Automatic Backup System for Virtualization Environment - Winarno, Idris; Sani, Muzaki Nurus (Politeknik Elektronika Negeri Surabaya (PENS), 2014)
Virtualization is a technology lately much discussed and considered as the proper way to cut costs in the construction of a data center. One example of the implementation of virtualization technologies is to using VMware. Another tools for virtualization are Xen and OpenVZ, but VMware is more flexible than Xen or OpenVZ because VMware can run a variety of operating systems. Although it has the advantage, virtualization technology also has a vital weakness, virtualization technologies could be analogous by putting all the eggs in a basket. This means that if the master server problem, all systems inside the virtual machine can not be used. However, it can be anticipated by provide backup facilities that run continually and automatically. VMware itself has had an application to backup/replicate virtual machines. However, that application is not free yet.This research has been design and creates a web-based software forbacking up virtual machines on VMware. So it made easier for users and admins to perform periodic backups of virtual machines. From the test results has been done, it can be seen that used disk type thin or zeroed thick make process backup faster, system canât work well when virtual machine has snapshot, scheduling system and restoring system has worked well, physical ability data storage influence system.Keywords: Virtual machine, virtualization, Vmware, Backup, DataÂ Center.